(3eNJUQ JGQjN OeTbs - (3eMeO Hf ecQe Hf Ydj, CHh GdaVd, LeGd GdOjf GHf efXhQ GdCfUGQj GdQhjaYj GdEaQjbj, J (B711 (3g` s; (3Ydj Hf GdMSf Hf gHI Gddg GdOeTbj , CHh GdbGSe, KbI GdOjf GHf YSGcQ,J (B600 (3g` s
(3ChdgG (B:s
(3JQLeI TgQ Hf MhTH s
(3BNQgG (B:s
(3JQLeI GdYHGS Hf eMeO Hf Ydi YHO Gddg Hf YHGS s
(3GfXQ Qbe (B451 (3, Qbe (B788 (3, Qbe (B1207 (3JGQjN s
(3fSNI SGOSI s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
Keywords: (3GdJGQjNs